DNA-supported palladium nanoparticles as a reusable catalyst for the copper- and ligand-free Sonogashira reaction. Issue 11 (9th May 2017) - Camacho, Ana Silvia; Martín-García, Iris; Contreras-Celedón, Claudia; Chacón-García, Luis; Alonso, Francisco
Abstract : Palladium nanoparticles on DNA have been shown to be an effective and reusable heterogeneous catalyst for the copper- and ligand-free Sonogashira coupling reaction of aryl iodides under mild conditions in air. Abstract : DNA nanotechnology has recently emerged as a powerful discipline with diverse applications. However, studies focused on the combination of DNA and metal nanoparticles for catalyst design are scanty. We have prepared a catalyst composed of palladium nanoparticles supported on DNA which has been characterised by TEM, SEM, EDX, UV, FTIR and XPS. The catalyst, mainly composed of Pd(ii ) and Pd(iv ) species in the form of oxides, has been effectual in the copper- and ligand-free Sonogashira–Hagihara coupling of aryl iodides with terminal aromatic and aliphatic alkynes. The products are obtained in 54–86% isolated yields using low catalyst loading (0.5 mol%) under mild conditions (65 °C) in methanol without air exclusion. Moreover, the catalyst can be easily recovered and reused in five cycles and shows better performance than an array of commercial palladium catalysts. The mechanistic aspects of the reaction are also tackled in detail.